Tonoplast proton pumps regulate nuclear spacing of female gametophytes via mediating polar auxin transport in Arabidopsis - Jiang, Yu-Tong; Zheng, Ji-Xuan; Li, Rong-Han; Wang, Yu-Chen; Shi, Jianxin; Ferjani, Ali; Lin, Wen-Hui (Frontiers in Plant Science, 2022)
The vacuole is an important organelle with multiple functions in plants, and the tonoplast that wraps the vacuole also plays essential roles in intracellular trafficking and ion homeostasis. Previous studies found that tonoplast proton pumps regulate embryo development and morphogenesis through their effects on vacuole biogenesis and distribution, as well as polar auxin transport and concomitant auxin gradient. However, the precise roles of the tonoplast proton pumps in gametophyte development remain unclear. Here we demonstrated that the lack of two types of tonoplast proton pumps or the absence of V-ATPase alone leads to abnormal development and nuclear localization of female gametophyte (FG), and slowed endosperm nuclei division after fertilization of the central cell. We further revealed that V-ATPase regulates auxin levels in ovules through coordinating the content and localization of PIN-FORMED 1 (PIN1) protein, hence influencing nuclear spacing between centra cell and egg cell, and subsequent endosperm development. Collectively, our findings revealed a crucial role of V-ATPase in auxin-mediated FG development in Arabidopsis and expanded our understanding of the functions of tonoplast proton pumps in seed plants reproductive development.